(untitled) (Journal of Interdisciplinary Insights, 2024)
The purpose of this paper is to study the internal and external effectiveness of equity transfer guarantee, through the review and analysis of relevant literature, combined with theoretical discussion and case analysis, to explore the application and influence of this system in legal practice. First of all, this paper summarizes the rules for the identification of equity transfer guarantee, and introduces the main viewpoints and disputes in the current research field. Secondly, the paper analyzes the existing laws on the internal and external effectiveness of equity transfer guarantee and limitations, as well as the problems and challenges in judicial practice. Thirdly, the paper discusses the application and influence of equity transfer guarantee in commercial financing, debt repayment and other practical scenarios, and analyzes its importance to the interests of the parties, market economy and social development. Finally, the paper puts forward solutions and suggestions for the internal and external effectiveness of equity transfer guarantee, including strengthening legal norms, improving judicial logic and optimizing practical operations, so as to promote the standardized application and healthy development of the system.